Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

A hermetically-isolated magnetic coupling triboelectric nanogenerator enabled self-powered in-line milk sterilization - Falun Liu; Shuangfeng Pan; Xiaoyu Su; Ziang Zhang; Jianfeng Ping; Xunjia Li; Yuxiang Pan (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Stage-Dependent Differences in Vertical Fault Transmissibility Control Segmented Hydrocarbon Accumulation along Strike-Slip Faults - Haitao Zhao; Chunguang Shen; Hongwei Ping; Jianjie Li; Ying Yang; Tengfei Su (Journal of Earth Science, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

Temperature-dependent regulation of benzeneacetaldehyde formation during black tea drying: Evidence from non-targeted metabolomics and an EGCG-modulated Maillard reaction model - Zisheng Han; Shengxiao Su; Wen Li; Tong Jia; Piaopiao Long; Jia-Ping Ke; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Metagenomics-based insights into the microbial community composition and quality characteristics development potentiality in traditional dry-cured ham - Ping Li; Yang Wang; Zhijie Bao; Xiaoyu He; Sunyan Wang; Xinlian Su; Wen Nie; Feiran Xu; Hui Zhou; Han Li; Baocai Xu (International Journal of Food Microbiology, 2026)

Unraveling grain quality in cereals: development, heat stress, and molecular mechanisms - Ping Li; Zheng Li; Jiangyue Su; Yanjie Lv; Shuhua Liao; Pu Wang; Shoubing Huang (Food Chemistry, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Influence of free surface on microwave-induced rock fracturing: An experimental and numerical study - Yanlong Zheng; Ziqiang Su; Gaofeng Zhao; Ping Che; Jianchun Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Lactic acid bacteria diversity in traditional fermented dairy products: Seasonal influences and microbial interactions - Jie Zhao; Yangbo Jiao; Ping Du; Dan Wang; Yu Li; Xin Su; Shuaili Zheng; Liang Zhou; Jiaqi Xie; Jie Yu (Food Bioscience, 2026)

Functional traits are plastic in response to intercropping, improving the stability of yield through temporal asynchrony - Hao Yang; Wei-Ping Zhang; Surigaoge Surigaoge; Hua-Sen Xu; Ye Su; Ragan M. Callaway; Long Li (Field Crops Research, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

Trade-offs between diversity and stability mediated by positive cohesion in sediment microbiomes under algal blooms - Ruyi Li; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; Yihan Wang; Misha Zhong; Qingchuan Chou; Meng Zhang; Haojie Su; Ping Xie (Algal Research, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Controls on heavy metal variability in a coastal mountainous river: Impacts of tides, typhoons, and anthropogenic activities - Yalong Li; Ni Su; Yun Zhao; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Shouye Yang (Journal of Geochemical Exploration, 2026)

Photothermal mediated bionanocomposite films with pasteurization-like activity for tangerine preservation - Linpin Luo; Wengang Cai; Zihan Qiu; Wenqiao Su; Yiya Ping; Bingzhi Li; Qianjin Liu; Jianlong Wang (Food Chemistry, 2026)

The Classification History of Lamiaceae and a Generic Synopsis in China - Si-Cheng Xu; Su Liu; Ya-Ping Chen; Yue Zhao; Fei Zhao; Chun-Lei Xiang; Bo Li (The Botanical Review, 2026)

A multifunctional 5-fluorouracil prodrug: synthesis, biological evaluation, and antitumor mechanism investigation - Ran Zhang; Liqing Tang; Jianglong He; Guanyu Jiang; Yingfei Su; Xueping Jiang; Ping Wu; Dongyang Zhang; Sitong Chen; Hao Li; Zhongzheng Gui (Molecular Diversity, 2026)

UVB-activated permanganate enables rapid emerging organic contaminants decontamination through synergistic HO• and reactive manganese species - Ping Li; Peng Su; Qixiao Lv; Qiuling Lu; Ying Xu; Xiangyang Hou; Jucai Xu; Jun Ma; Tao Yang (Water Research, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Microbial dynamics of wild and cultured Sinularia flexibilis: Implications for coral aquaculture - Li-Guo Zheng; Kuei-Hung Lai; Ping-Jyun Sung; You-Ying Chen; Jimmy Kuo; Jui-Hsin Su; Mohamed El-Shazly (Aquaculture, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Algae: A considerable regulator of methylmercury in mercury-contaminated paddy fields - Ling Su; Guangjun Luo; Tianrong He; Pan Wu; Ping Li; Deliang Yin; Yuping Xiang; Xian Zhou (Journal of Environmental Sciences, 2026)

Sensitive detection of carbofuran in agricultural products using a metal-phenolic network-coated aggregation-induced emission Luminogen nanoprobe-based lateral flow immunoassay - Liu Su; Ganggang Zhang; Xiaocui Lai; Ping Li; Cong Liu; Weihua He; Gan Zhang; Weihua Lai; Shengliang Deng (Food Chemistry, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Analysis of clinical characteristics and prognostic factors in AIDS complicated by cryptococcal meningitis - Yanlan Liang; Xiyang Dong; Yong Deng; Zhende Lin; Caixia Zheng; Jiaxuan Li; Yijie Lin; Huatang Zhang; Xing Wang; Wenwu Lin; Wencong Hong; Su Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

High-intensity fish disturbance reduces ecosystem multifunctionality by diminishing planktonic bacterial diversity and network complexity - Shangsheng Sun; Jianfeng Chen; Qingyang Rao; Yuwei Wang; Ruyi Li; Misha Zhong; Yihan Wang; Zengliang Jian; Chaokun Wang; Yafang Qin; Yulian Chu; Ping Xie; et al. (Biological Conservation, 2025)

Unraveling the functional complexity of the locus coeruleus-norepinephrine system: insights from molecular anatomy to neurodynamic modeling - Chun-Wang Su; Fan Yang; Runchen Lai; Yanhai Li; Hadia Naeem; Nan Yao; Si-Ping Zhang; Haiqing Zhang; Youjun Li; Zi-Gang Huang (Cognitive Neurodynamics, 2025)

Beyond biodiversity: The more essential role of multi-trophic network complexity for predicting ecosystem multifunctionality under multiple stressors - Shangsheng Sun; Haojie Su; Qingyang Rao; Jianfeng Chen; Yafang Qin; Yongchao Peng; Chaoyue Cheng; Misha Zhong; Ruijing Ma; Yuwei Wang; Yihan Wang; Zengliang Jian; et al. (Water Research, 2025)

The soil organic carbon sequestration potential and formation efficiency of China’s temperate grasslands - Lu Yang; Ping Li; Yuntao Wu; Nairsag Jalaid; Weixing Liu; Xiaoqiang Liu; Ziyang Peng; Junsheng Huang; Xiaoxia Zhao; Lubing Jiang; Zhaoyu Peng; Sen Yang; et al. (Science Bulletin, 2025)

Microplastic aging and plastisphere succession in mangrove sediments: Mechanisms, microbial interactions, and degradation potential - Yuanyuan Su; Jun Lei; Xiaoping Diao; Licheng Peng; Lianzheng Yin; Yongqiang Qin; Wen Zhang; Ping Li (Journal of Hazardous Materials, 2025)

Overyielding of maize cultivar mixtures is associated with interaction-driven depth partitioning of roots - Ye Su; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Monitoring the growth status of winter wheat by using the machine learning algorithm and the fusion of spectral and texture features derived from the UAV remote sensing - YiMing Su; XiaoBin Yan; Hao Li; ZiHao Liang; ShuangMei Zhao; Ping Chen; Zhen Zhang; XingXing Qiao; Yu Zhao; MeiChen Feng; Fahad Shafiq; XiaoYan Song; et al. (Computers and Electronics in Agriculture, 2025)

Furofuran and tetrahydrofuran lignans from Lancea tibetica - Wenbo Li; Fuhua Zhu; Lu Tang; Jun Xu; Xiaoying Zhang; Zhicheng Duan; Wei Zhang; Ping Hai; Yongbiao Zheng; Haiqing Liu; Xia Li; Yanfang Su (Phytochemistry, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Surface chlorine doping activates highly stable Cu2O(111) facets for enhanced CO2 photoreduction - Ning Li; Ping Zhang; Reyila Tuerhong; Yongchong Yu; Yapeng Lan; Yu Zhang; Xiaoping Su; Lianbiao Zhao; Lijuan Han; Xiaotian Wang; Hengjiao Gao (Chemical Engineering Journal, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

Fragments of ancient continental lithospheric mantle in the Mogok metamorphic Belt, Northern Myanmar: Re–Os isotope and platinum group element constraints - Qing-Hua Zhang; Bin Su; Yi Chen; Victoria Pease; Tou-Ping Peng; Zhu-Yin Chu; Yi-Bing Li; Kai-Hui Shi; Si Chen (Precambrian Research, 2025)

Gas Hydrate Exploration Using Deep-Towed Controlled-Source Electromagnetics in the Shenhu Area, South China Sea - Jianping Li; Zhongliang Wu; Xi Chen; Jian’en Jing; Ping Yu; Xianhu Luo; Mingming Wen; Pibo Su; Kai Chen; Meng Wang; Yan Gao; Yao Zhang (Journal of Marine Science and Engineering, 2025)
This study presents the first application of a deep-towed transmitter–receiver marine controlled-source electromagnetic (TTR-MCSEM) system for gas hydrate exploration in the Shenhu area of the South China Sea. High-resolution electromagnetic data were acquired along a 13 km transect using dynamic source–receiver offsets and a 500 A transmitter. The results reveal the following: (1) unprecedented near-seafloor resolution (20~100 m) for the precise delineation of hydrate-bearing caprock, surpassing conventional ocean-bottom electromagnetic systems; (2) laterally continuous high-resistivity anomalies (~10 Ω·m) extending from the base of the gas hydrate stability zone to the seafloor, which correlate with seismic bottom-simulating reflector (BSR) distributions and suggest heterogeneous hydrate saturation; and (3) fault-controlled fluid migration pathways that supply hydrate reservoirs and lead to seabed methane seepage at structural highs. Through 2D inversion, we show that the inverted resistivity values (~10 Ω·m) are slightly higher than those obtained from resistivity logs (~5 Ω·m). Saturation values derived from inverted resistivity exhibit remarkable consistency with well-log-based measurements. The high efficiency of the system confirms its potential for the transformative quantitative assessment of hydrate systems, seafloor massive sulfides, and marine geohazards.

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

The feasibility and prospects of coal mine water as a cooling medium for data centers - Zaining Li; Chunhui Zhang; Peidong Su; Guifeng Zhao; ZePeng Wang; YiYun Li; YanXin Li; Mengna Wang; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

Occurrence, ecology and health risk assessment of organophosphate triesters and diesters in surface and ground water from southwest of China - Tianyang Lan; Li Zhao; Jie Xiong; Ruonan Wang; Ping Yang; Weiyi Sun; Shijun Su; Zhiwei Gan; Zhiren Tian (Environmental Research, 2025)

The Impact of Biochar Combined with Submerged Plants on the Storage and Stability of Rhizospheric Soil Organic Carbon in Wetlands - Yang Yu; Sheng-Nan Du; Bang-Ping Deng; Ling-Kan Su; Juan-Ying Li (Wetlands, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Selective and controllable mechanism of the temperature field in skin tissue under radiofrequency heating: finite element analysis and ex-vivo pig skin experiments - Ping Zhu; Chuanqi Xie; Kai Li; Fangjie Shu; Liqiang Li; Zhaodi Su; Yue Xue (Journal of Thermal Biology, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Designing flexible aliphatic linker based molecular imprinted covalent organic framework for rapid and selective extraction and detection of trace zearalenone - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2025)

Incorporating atomic-level center into porphyrin-based COF for photocatalytic H2 evolution - Guo-Wei Guan; Su-Tao Zheng; Li-Ping Zhang; Si-Yu Hou; Xiang-Yu Liu; Qing-Yuan Yang (Chemical Engineering Journal, 2025)

Dipole-polarized Cu–Ni atomic interfaces for synergistic enhancement and steering of overall nitrogen photofixation - Longjian Li; Ping Zhang; Reyila Tuerhong; Yongchong Yu; Keyi Chai; Lianbiao Zhao; Xiaoping Su; Lijuan Han (Chemical Engineering Journal, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Warming Enhances the Effects of Acidification on Aquatic Biota: A Global Meta‐Analysis - Zengliang Jian; Misha Zhong; Ruyi Li; Haojie Su; Qingyang Rao; Yihan Wang; Chaokun Wang; Shangsheng Sun; Jianfeng Chen; Ping Xie (Global Ecology and Biogeography, 2025)
Aim Global elevated atmosphere CO 2 concentration‐induced acidification poses a great threat to aquatic organisms worldwide. However, a comprehensive understanding of the response variability to acidification is still lacking, especially in the context of concurrent global warming. Addressing the response patterns of aquatic biota to acidification under the context of warming can facilitate the identification and prediction of probable consequences of global climate change. Location Global. Time Period 1996–2024. Major Taxa Studied Aquatic biota. Methods We performed a meta‐analysis by synthesising 221 studies containing 3669 observations to summarise the effects of CO 2 on multiple aquatic biota, including primary producers, consumers, and decomposers. We further examined the effects of different ecosystems, experimental venue, CO 2 concentration, and ambient experimental temperature on the response magnitude. Results Acidification had significant positive effect on primary producers and decomposers, yet significant negative effect on consumers. We found that invertebrates were the most negatively affected of all organisms, and the marine ecosystems are suffering more severity of acidification than freshwater ecosystems. We further found that the response magnitude showed a significant dose effect, indicating that reducing greenhouse gas emissions would minimise the impact of acidification. In addition, we found that higher temperatures enhanced the sensitivity of primary producers to acidification, suggesting that global climate warming may interact with acidification in a synergistic way. Main Conclusions Our results showed that distinct trophic levels showed significant differences in the response direction and magnitude. Specifically, the consumer is generally the most sensitive trophic level that is negatively affected by acidification. We emphasise that the simultaneous exposure of primary producers to anthropogenic stressors associated with acidification and warming is expected to produce interactions that may potentially reinforce the negative consequences, which is key to predicting and mitigating the acidification effect under future climate change scenarios.

Recent progress in intrinsic self-healing polymer materials: Mechanisms, challenges and potential applications in oil and gas development - Shunming Zhou; Ning Qi; Zehui Zhang; Ping Jiang; Aihua Li; Yixin Lu; Xuhang Su (Chemical Engineering Journal, 2025)

Restoring turbid eutrophic shallow lakes to a clear-water state by combined biomanipulation and chemical treatment: A 4-hectare in-situ experiment in subtropical China - Bo Li; Deyuan Chen; Jichong Lu; Suxia Liu; Jiale Wu; Lei Gan; Xiaoqin Yang; Xiaolin He; Hu He; Jinlei Yu; Ping Zhong; Yali Tang; et al. (Journal of Environmental Management, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Role of microbiota and its ecological succession on flavor formation in traditional dry-cured ham: a review - Ping Li; Zhijie Bao; Yang Wang; Xinlian Su; Hui Zhou; Baocai Xu (Critical Reviews in Food Science and Nutrition, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

Litter functional dissimilarity accelerates carbon and nitrogen release from the decomposition of straw but not root in maize/legume intercropping - Surigaoge Surigaoge; Hao Yang; Dario Fornara; Ye Su; Yu-He Du; Su-Xian Ren; Wei-Ping Zhang; Long Li (Plant and Soil, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Remediation of multi-metal(loid) contaminated soils using Mn-modified biochar: Mechanistic insights and influencing factors - Jin-Zhou Su; Xiao-Ning Feng; Ping Xiang; Zhao-Lai Guo; Li-Xin Li; Tao Zhang; Jun-Bao Yu (Process Safety and Environmental Protection, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Structurally diverse ent-clerodanoids from the aerial parts of Isodon scoparius - Xue-Chun Jiang; Kun Hu; Xue Bai; Xing-Ren Li; Bing-Chao Yan; Su-Ping Chen; Xiao-Nian Li; Han-Dong Sun; Pema-Tenzin Puno (Phytochemistry, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Calixarene incorporated molecular imprinting on covalent organic framework for supramolecular recognition and specific extraction of citrinin - Li-Hong Su; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Multi-omics analysis unravels the underlying mechanisms of the escape response of the common strain black carp (Cyprinus carpio var. baisenensis) - Yuanfeng Xu; Ping Dong; Daniel Yohannes Sewo; Shengyan Su; Jianlin Li; Wenrong Feng; Yu Liao; Yongkai Tang (Aquaculture International, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Physical and mechanical characterization of solid waste collected from rural areas of China: Experimental study - Yu-Ping Li; Baoyun Fan; Le Cheng; Jianyong Shi; Xiulei Li; Lianghu Su; Zeeshan Khursheed (Process Safety and Environmental Protection, 2024)

Enhancing reductive dechlorination of trichloroethylene in bioelectrochemical systems with conductive materials - Su-Hao Chen; Zheng-Tao Li; Chun-Yu Lai; He-Ping Zhao (Environmental Research, 2024)

7S,8R-Dihydroxydeepoxysarcophytoxide: A natural dihydrofuranocembranoid from the octocoral Sarcophyton stellatum - Jyh-Horng Sheu; Li-Guo Zheng; You-Ying Chen; Su-Ying Chien; Ping-Jyun Sung (Phytochemistry Letters, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Synthesis and characterization of Ce-BiOBr/Bi2S3 catalyst with enhanced catalytic activity for organic dye reduction under dark - Mengistu Tadesse Mosisa; Pengkun Zhang; Binghong Wu; Longyan Chen; Zhengjie Su; Ping Li; Hanya Zhang; Ambar Farooq; Ting Huang; Adugna Boke Abdeta; Osman Ahmed Zelekew; Dong-Hau Kuo; et al. (Journal of Environmental Chemical Engineering, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Co2+ coordination-assisted molecularly imprinted covalent organic framework for selective extraction of ochratoxin A - Li-Hong Su; Hai-Long Qian; Cheng Yang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Revealing the potential of quantum dot nanomaterials in photocatalytic applications - Le Zhao; Ping Zhang; Longjian Li; Ning Li; Reyila Tuerhong; Xiaoping Su; Wanhong Sun; Lijuan Han (Chemosphere, 2024)

Deciphering the influence of salinity stress on the biological aniline degradation system: Pollutants degradation performance and microbial response - Qi He; Bin Tan; Meng Li; Junhao Su; Bing Lin; Nan-ping Wu; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Environmental Research, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Retrieval of subsurface dissolved oxygen from surface oceanic parameters based on machine learning - Bo Ping; Yunshan Meng; Fenzhen Su; Cunjin Xue; Zhi Li (Marine Environmental Research, 2024)

The role of OsBZR4 as a brassinosteroid-signaling component in mediating atrazine and isoproturon degradation in rice - Xiangning Su; Chuan Ying Li; Xue Song Liu; Yu Ping Zhang (Journal of Hazardous Materials, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Rural energy transition in the context of rural revitalization and carbon neutrality: improved multi-criteria-based decision-making - Tie-zhi Li; Pan Du; Xin-ping Wang; Chang Su (Mitigation and Adaptation Strategies for Global Change, 2024)

Spatio-temporal patterns of intense tropical cyclones in the Western North Pacific over the past 1600 years - Liang Zhou; Rumeng Hao; Mingchen Li; Yan Su; Shu Gao; Yang Yang; Zhixiong Shen; Jianjun Jia; Ya Ping Wang (Marine Geology, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

Integrating molecular imprinting into flexible covalent organic frameworks for selective recognition and efficient extraction of aflatoxins - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

Application of g-C3N4-based photocatalysts for N2 photofixation - Longjian Li; Ping Zhang; Ning Li; Tuerhong Reyila; Yongchong Yu; Xiaoping Su; Cheng Peng; Lijuan Han (Journal of Environmental Chemical Engineering, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Iridoid and lignan glycosides from Lancea tibetica - Yi Zhu; Junlin Wang; Lu Tang; Yuxin Shang; Weiyi Zhao; Wei Zhang; Ping Hai; Yongbiao Zheng; Wenbo Li; Yanfang Su (Phytochemistry Letters, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Effects of Seasonal Photoperiod on Growth, Lipid Metabolism, and Antioxidant Response in the Huanghe Carp (Cyprinus carpio haematopterus) - Wenqian Wang; Shengyan Su; Ping Dong; Wenrong Feng; Jianlin Li; Chengfeng Zhang; Yongkai Tang (Fishes, 2023)
Photoperiod is one of the most important environmental cues for organisms, and it plays a crucial role in regulating feeding, behavior, growth, and metabolism. However, seasonal photoperiods are often overlooked in carp culture or experiments, with a poorly understood effect on lipid metabolism and oxidative stress in fish. To explore the effects of seasonal photoperiods, we exposed Huanghe carp (Cyprinus carpio haematopterus) to summer photoperiod (14 h light:10 h dark) and winter photoperiod (10 h light:14 h dark) daylight conditions in an eight-week experiment. Our results suggested that the winter photoperiod significantly increased the liver TG level as well as the transcript levels of genes related to lipid synthesis, indicating that the lipid metabolism in Huanghe carp liver was enhanced compared to summer photoperiod conditions, and that lipid deposition may be responsible for the increase in body weight level and hepatosomatic index. Additionally, MDA, GSH, GSH-PX, and T-AOC levels were significantly elevated in the liver of fish under the winter photoperiod, suggesting that Huanghe carp responded to winter photoperiod exposure-induced oxidative stress in the liver by enhancing the antioxidant response. Based on transcriptome analysis, the winter photoperiod activated hepatic autophagy response and the FOXO signaling pathway in Huanghe carp. Combined with the correlation analysis, the Huanghe carp maintains the physiological health of the liver by activating the FOXO signaling pathway-mediated cell cycle regulation and autophagy response in response to oxidative stress during winter photoperiod exposure. Our study provides the first evidence for the physiological regulation of the liver in Huanghe carp under seasonal photoperiod stimulation.

Recent advances in tea seeds (Camellia Sinensis (L.) O. Kuntze): Active ingredients, health effects, and potential applications - Su Zhou; Zhiying Li; Haizhao Song; Hao Hu; Shicheng Ma; Yike Tao; Zhilong Hao; Xinyu Feng; Yani Pan; Shuying Gong; Fangyuan Fan; Ping Chen; et al. (Trends in Food Science & Technology, 2023)

Paternal cadmium exposure induces glucolipid metabolic reprogramming in offspring mice via PPAR signaling pathway - Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Xiaofei Wang; Yamin Li; Jieping Song; JingFan Shao; Ping Su (Chemosphere, 2023)

Surface imprinted-covalent organic frameworks for efficient solid-phase extraction of fluoroquinolones in food samples - Li-Hong Su; Hai-Long Qian; Cheng Yang; Chuanxi Wang; Zhenyu Wang; Xiu-Ping Yan (Journal of Hazardous Materials, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Bioelectrochemical system accelerates reductive dechlorination through extracellular electron transfer networks - Su-Hao Chen; Zheng-Tao Li; He-Ping Zhao (Environmental Research, 2023)

Synergization of an endoplasmic reticulum-targeted iridium(III) photosensitizer with PD-L1 inhibitor for oral squamous cell carcinoma immunotherapy - Jia-Ying Zhou; Qing-Hua Shen; Xiao-Jing Hong; Wu-Ya Zhang; Qiao Su; Wu-Guo Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2023)

Potentially migrating and residual components of biochar: Effects on phosphorus adsorption performance and storage capacity of black soil - Ping Xue; Renjie Hou; Qiang Fu; Tianxiao Li; Jinwu Wang; Wenqi Zhou; Weizheng Shen; Zhongbin Su; Yijia Wang (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Irisin Attenuates Apoptosis Following Ischemia–Reperfusion Injury Through Improved Mitochondria Dynamics and ROS Suppression Mediated Through the PI3K/Akt/mTOR Axis - Ji-fei Liu; Gang Su; Li-xia Chen; Juan-ping Zhou; Juan Gao; Jia-jia Zhang; Qiong-hui Wu; Wei Chen; De-yi Chen; Zhen-chang Zhang (Molecular Neurobiology, 2023)

Determinants affecting the blood mercury levels of preschool children in Shanghai, China: A cross-sectional study - Xi Xu; Yu-Qing Wang; Chen-Yin Dong; Chun-Ping Hu; Li-Na Zhang; Zhen-Yan Gao; Min-Ming Li; Su-Su Wang; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Four cases of reported adverse effects from black boletoi, Anthracoporus nigropurpureus (Boletaceae) mushroom ingestion - Jing Ma; Jing Xia; Hai-Jiao Li; Lin-Jie Su; Rou Xue; Shuai Jiang; Tai-Jie Yu; Yi Liu; Li-Ping Tang (Toxicon, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Simultaneously achieving enhanced water adsorption and rapid adsorbed hydroxyl transfer toward MXene-based materials for highly efficient alkaline electrocatalytic hydrogen evolution - Yang Meng; Ping Zeng; Xiao-Yu Yang; Zhan Liu; Xiao-Yun Li; Cui-Fang Ye; Yu Li; Jin-Ping Liu; Bao-Lian Su; Li-Hua Chen; Yi-Long Wang (Chemical Engineering Journal, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

First report of Fusarium foetens causing root rot on lavender (Lavandula angustifolia) in China - Xue-Jun Wei; Bing-Guo Jia; Xing Wang; Nan-Yang Li; Su-Na Wang; Li Li; Ai Zhang; Hao-Tian Zhang; Li-Ping Wang (Journal of Plant Pathology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

Effects of different crop rotations on the incidence of cotton Verticillium wilt and structure and function of the rhizospheric microbial community - Weisong Zhao; Shezeng Li; Lihong Dong; Peipei Wang; Xiuyun Lu; Xiaoyun Zhang; Zhenhe Su; Qinggang Guo; Ping Ma (Plant and Soil, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Associations of blood metals with liver function: Analysis of NHANES from 2011 to 2018 - Wenjie Li; Xinyan Li; Jing Su; Han Chen; Ping Zhao; Haisheng Qian; Xin Gao; Qiang Ye; Guoxin Zhang; Xuan Li (Chemosphere, 2023)

Experimental investigation on dynamic characteristics of fiber-binder modified subgrade filler after freezing-thawing under cyclic loading - Jiahui Wang; Yan Li; Ping Yang; Xianzhang Ling; Yingying Zhao; Lei Su (Transportation Geotechnics, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Gas-in-place and its influence factors of the upper Paleozoic coal-bearing shale in the Qinshui Basin, China - Chengang Lu; Ping Gao; Gang Li; Yue Feng; Xiaorong Qu; Yufei Su; Xianming Xiao (Frontiers of Earth Science, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Enhanced stability and combustion performance of AlH3 in combination with commonly used oxidizers - Ming-Hui Yu; Su-Lan Yang; Wu-Xi Xie; Zhao-Yang Zhu; He-Ping Li; Qi-Long Yan (Fuel, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

A water-soluble polysaccharide from Eucommia folium: the structural characterization and anti-tumor activity in vivo - Zhi-Qian Yan; Su-Yun Ding; Pei Chen; Hui-Ping Liu; Meng-Li Chang; Shu-Yuan Shi (Glycoconjugate Journal, 2022)

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Comparative transcriptome analyses identify genes involved into the biosynthesis of forsythin and forsythoside A in Forsythia suspensa - Wang Jun Yuan; Su Ping Zhang; Zhi Yin He; Yan Xia He; She Qi He; Li Jun Liu; Xin Sun; Qin Li (Functional & Integrative Genomics, 2022)

The Role of Post-Translational Modifications on the Structure and Function of Tau Protein - Haiqiong Ye; Yue Han; Ping Li; Zhengding Su; Yongqi Huang (Journal of Molecular Neuroscience, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Is Zooplankton Body Size an Indicator of Water Quality in (Sub)tropical Reservoirs in China? - Li Wang; Jun Chen; Haojie Su; Xufa Ma; Zhixu Wu; Hong Shen; Jia Yu; Jiarui Liu; Yao Wu; Guangyi Ding; Ping Xie (Ecosystems, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Eutrophication and predation mediate zooplankton diversity and network structure - Yun Li; Rong Wang; Haojie Su; Jianjun Wang; Ping Xie; Feizhou Chen (Limnology and Oceanography, 2022)
Anthropogenic activities such as eutrophication and fishing have prominent effects on freshwater ecosystems. However, the ways in which ecosystem function and biodiversity respond to multiple drivers from eutrophication and top‐down predation remains inconclusive. We studied zooplankton communities in 102 subtropical shallow lakes in the eastern plain of China and further examined the joint effects of nutrient enrichment and predation on biodiversity and ecological networks. We found that alpha diversity was negatively influenced by nutrient conditions (such as total phosphorus and total nitrogen [TN]), whereas beta diversity (β‐diversity) was positively related to nutrients and was also structured by omnivorous fish showing a unimodal pattern. Furthermore, the network skewness of zooplankton increased with nutrient enrichment, especially TN, and was negatively related to omnivorous fish. This skewness is more sensitive than β‐diversity, whereas negative skew is primarily caused by omnivorous fish. Our results demonstrated that top‐down effects were dominant for zooplankton communities and resulted in structural adjustment of zooplankton communities, mainly with an increase in fish predation. A negative skewed network indicates the presence of more generalist species and stronger connections among the zooplankton assemblages, as well as decreased β‐diversity.

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Association between serum folate levels and blood concentrations of cadmium and lead in US adults - Zuxiang Wu; Huan Hu; Chenxi Wang; Ji Wu; Yurong Xiong; Yang Fu; Xiaoshu Cheng; Hai Su; Ping Li (Environmental Science and Pollution Research, 2022)

Synergistic inhibitory effect of berberine and icotinib on non-small cell lung cancer cells via inducing autophagic cell death and apoptosis - Ping Chen; Chun-Hua Dai; Zhi-Hao Shi; Yi Wang; Jian-Nong Wu; Kang Chen; Jin-Yu Su; Jian Li (Apoptosis, 2021)

Rapid visual genotyping method for germline mutants with small genomic fragment deletion by allele-specific PCR and lateral flow nucleic acid biosensor - Qiuju Su; Xiang Zhou; Tianwen Wu; Kui Li; Wentao Xu; Zhenyu Lin; Ping Shen; Bang Liu (Molecular Biology Reports, 2021)

Serum levels of polychlorinated biphenyls and stroke risk among Chinese: a hospital-based case–control study - Ping Li; Ying Dan; Shuangying Li; Qiaolian Zhang; Ya Su; Mei Lu (Acta Neurologica Belgica, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Migration and transformation of heavy metals in hyperaccumulators during the thermal treatment: a review - Wei Su; Xinyan Li; Hongshuo Zhang; Yi Xing; Ping Liu; Changqing Cai (Environmental Science and Pollution Research, 2021)

Research on displacement prediction of step-type landslide under the influence of various environmental factors based on intelligent WCA-ELM in the Three Gorges Reservoir area - Yong-gang Zhang; Xin-quan Chen; Rao-ping Liao; Jun-li Wan; Zheng-ying He; Zi-xin Zhao; Yan Zhang; Zheng-yang Su (Natural Hazards, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

The highly conserved rps12 gene in ferns provides strong evidence for decreased substitution rates in the inverted repeat region - Jingyao Ping; Aimin Li; Peipei Feng; Ming Zhu; Yingjuan Su; Ting Wang (Plant Systematics and Evolution, 2021)

Evidence-based Customized Ankle-Foot Orthosis with Energy Storage - Chih-Chun Lin; Chien-Hsien Yeh; Yi-Chun Tsai; Li-Chieh Kuo; Hsiu-Yun Hsu; Ping-Han Chuang; Kai Chang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Starch bio-template synthesis of W-doped CeO2 catalyst for selective catalytic reduction of NOx with NH3: influence of ignition temperature - Zhi-Bo Xiong; Zhen-Zhuang Li; Yan-Ping Du; Cheng-Xu Li; Wei Lu; Su-Le Tian (Environmental Science and Pollution Research, 2021)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Spatial and Temporal Distributions of Atmospheric CO2 in East China Based on Data from Three Satellites - Bozhen Li; Gen Zhang; Lingjun Xia; Ping Kong; Mingjin Zhan; Rui Su (Advances in Atmospheric Sciences, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

Qualitative and Quantitative Analyses of the Colonization Characteristics of Bacillus subtilis Strain NCD-2 on Cotton Root - Lihong Dong; Qinggang Guo; Peipei Wang; Xiaoyun Zhang; Zhenhe Su; Weisong Zhao; Xiuyun Lu; Shezeng Li; Ping Ma (Current Microbiology, 2020)

The bHLH gene family and its response to saline stress in Jilin ginseng, Panax ginseng C.A. Meyer - Lei Zhu; Mingzhu Zhao; Mengyao Chen; Li Li; Yue Jiang; Sizhang Liu; Yang Jiang; Kangyu Wang; Yanfang Wang; Chunyu Sun; Jing Chen; Ping Chen; et al. (Molecular Genetics and Genomics, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Genome-wide identification, phylogeny, and expression analysis of Sec14-like PITP gene family in sugarcane - Mao Hua-ying; Wang Wen-ju; Su Wei-hua; Su Ya-chun; Liu Feng; Li Cong-na; Wang Ling; Zhang Xu; Xu Li-ping; Que You-xiong (Plant Cell Reports, 2019)

Sulfide Rb-Sr and Zircon U-Pb Dating of the ~825 Ma Liujiaping Cu-Zn deposit in the Northwestern Yangtze Block (China) and its tectonic implications - Yan-Ping Su; Bao-Lin Zhang; Hui-Zhong Li; Ya-Na Miao; Xiao-Li Shen (International Geology Review, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Quantifying the ecological stability of artificial aquatic ecosystems: a case study of an artificial lake in Chengdu, China - Fang-Fang Chen; Gong-Ping Su; Hai-Yan Mou; Xuan Liang; Yi Chen; Tian-Qi Ao; Wen-Qing Chen; Yun-Zhen Li (Aquatic Sciences, 2019)

Dietary strategies to reduce the oral bioaccessibility of cadmium and arsenic in rice - Ping Zhuang; Shuo Sun; Feng Su; Feng Li; Xiaofang Zhou; Peng Mao; Yingwen Li; Zhian Li; Chaosheng Zhang (Environmental Science and Pollution Research, 2018)

Chemical characteristics, source apportionment, and regional transport of marine fine particles toward offshore islands near the coastline of northwestern Taiwan Strait - Cheng-Chih Chang; Chung-shin Yuan; Tsung-Chang Li; Yen-Lung Su; Chuan Tong; Shui-Ping Wu (Environmental Science and Pollution Research, 2018)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

Ascorbic acid inhibits cadmium-induced disruption of the blood-testis barrier by regulating oxidative stress-mediated p38 MAPK pathways - Na Chen; Ping Su; Mei Wang; Ya-Min Li (Environmental Science and Pollution Research, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Network analysis of microRNAs, transcription factors, and target genes involved in axon regeneration - Li-ning Su; Xiao-qing Song; Zhan-xia Xue; Chen-qing Zheng; Hai-feng Yin; Hui-ping Wei (Journal of Zhejiang University-SCIENCE B, 2018)

A Semi-analytical Model for Pressure-Dependent Permeability of Tight Sandstone Reservoirs - Su-Yang Zhu; Zhi-Min Du; Chuan-Liang Li; Alireza Salmachi; Xiao-Long Peng; Chao-Wen Wang; Ping Yue; Peng Deng (Transport in Porous Media, 2018)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Oxidative stress promotes myocardial fibrosis by upregulating KCa3.1 channel expression in AGT-REN double transgenic hypertensive mice - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2017)

Neuroprotection of dexmedetomidine against propofol-induced neuroapoptosis partly mediated by PI3K/Akt pathway in hippocampal neurons of fetal rat - Ning Zhang; Quan-ping Su; Wei-xia Zhang; Nian-jun Shi; Hao Zhang; Ling-ping Wang; Zhong-kai Liu; Ke-zhong Li (Journal of Zhejiang University-SCIENCE B, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Network analysis identifies common genes associated with obesity in six obesity-related diseases - Li-ning Su; Yan-bing Wang; Chun-guang Wnag; Hui-ping Wei (Journal of Zhejiang University-SCIENCE B, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Effects of Organic Acids and Sylvite on Phytoextraction of 241Am Contaminated Soil - Ping Wang; Liang Du; Zhaoyi Tan; Rongbo Su; Taowen Li (Bulletin of Environmental Contamination and Toxicology, 2017)

Identification of neuron-related genes for cell therapy of neurological disorders by network analysis - Li-ning Su; Xiao-qing Song; Hui-ping Wei; Hai-feng Yin (Journal of Zhejiang University-SCIENCE B, 2017)

Oral bioaccessibility and human exposure assessment of cadmium and lead in market vegetables in the Pearl River Delta, South China - Ping Zhuang; Yingwen Li; Bi Zou; Feng Su; Chaosheng Zhang; Hui Mo; Zhian Li (Environmental Science and Pollution Research, 2016)

Protective role of ACE2-Ang-(1–7)-Mas in myocardial fibrosis by downregulating KCa3.1 channel via ERK1/2 pathway - Li-Ping Wang; Su-Jing Fan; Shu-Min Li; Xiao-Jun Wang; Jun-Ling Gao; Xiu-Hong Yang (Pflügers Archiv - European Journal of Physiology, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

TGF-β1 and TIMP-4 regulate atrial fibrosis in atrial fibrillation secondary to rheumatic heart disease - Yu Sun; Zi-Yang Huang; Zhen-Hua Wang; Cui-Ping Li; Xian-Liang Meng; Yun-Jiao Zhang; Feng Su; Nan Ma (Molecular and Cellular Biochemistry, 2015)

AcSKP1, a multiplex PCR-based co-dominant marker in complete linkage disequilibrium with the male-fertility restoration (Ms) locus, and its application in open-pollinated populations of onion - Yu Meng Huo; Bing Jiang Liu; Yan Yan Yang; Jun Miao; Li Min Gao; Su Ping Kong; Zhen Bao Wang; Hidemi Kitano; Xiong Wu (Euphytica, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

Morin Inhibits Sortase A and Subsequent Biofilm Formation in Streptococcus mutans - Ping Huang; Ping Hu; Su Yun Zhou; Qian Li; Wei Min Chen (Current Microbiology, 2014)

Molecular cloning and characterization of two pathogenesis-related β-1,3-glucanase genes ScGluA1 and ScGluD1 from sugarcane infected by Sporisorium scitamineum - Ya-chun Su; Li-ping Xu; Ban-tong Xue; Qi-bin Wu; Jin-long Guo; Lu-guang Wu; You-xiong Que (Plant Cell Reports, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of serum adiponectin level and SNP +45 polymorphism of adiponectin gene on myocardial fibrosis - Cheng-jun Yan; Su-mei Li; Qiang Xiao; Yan Liu; Jian Hou; Ai-fang Chen; Li-ping Xia; Xiu-chang Li (Journal of Zhejiang University-SCIENCE B, 2013)

Label-free quantitative proteomics analysis of dormant terminal buds of poplar - De-Li Ning; Chang-Cai Liu; Jin-Wen Liu; Zhuo Shen; Su Chen; Feng Liu; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2013)

Warnstorfia exannulata, an aquatic moss in the Arctic: seasonal growth responses - Cai-Qing Guo; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Yi-Feng Yao; Lin-Gen Bian; Su-Ping Li; Cheng-Sen Li (Climatic Change, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial-temporal evolution pattern of agricultural productivity in northwestern sichuan plateau - Li Peng; Chun-jiang Su; Lian Sun; Ping Li; Yan Fang; Wei Liu; Xiao-lan Wang (Journal of Mountain Science, 2013)

Identification of two SCAR markers co-segregated with the dominant Ms and recessive ms alleles in onion (Allium cepa L.) - Yan Yan Yang; Yu Meng Huo; Jun Miao; Bing Jiang Liu; Su Ping Kong; Li Min Gao; Chang Liu; Zhen Bao Wang; Yasuki Tahara; Hidemi Kitano; Xiong Wu (Euphytica, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

STAT1 activation by venous malformations mutant Tie2-R849W antagonizes VEGF-A-mediated angiogenic response partly via reduced bFGF production - Yi-Hsien Huang; Ming-Ping Wu; Shin-Chen Pan; Wu-Chou Su; Yi-Wen Chen; Li-Wha Wu (Angiogenesis, 2013)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Effects of different organic residues on rice yield and soil quality - Li Peng; Wei Liu; Chunjiang Su; Ping Li; Yan Fang; Xiaolan Wang; Lian Sun (Journal of Mountain Science, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

The evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - HUI-XING SONG; SU-PING GAO; MING-YAN JIANG; GUANG-LI LIU; XIAO-FANG YU; QI-BING CHEN (Journal of Genetics, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

Effects of SCR-3 on the immunosuppression accompanied with the systemic inflammatory response syndrome - Jun Li; Jie Niu; Shan Ou; Zhan-Yong Ye; Deng-Qun Liu; Feng-Chao Wang; Yong-Ping Su; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2012)

Chemical and pharmacological studies of Oplopanax horridus, a North American botanical - Tyler Calway; Guang-Jian Du; Chong-Zhi Wang; Wei-Hua Huang; Jing Zhao; Shao-Ping Li; Chun-Su Yuan (Journal of Natural Medicines, 2012)

Down-regulation of β3-integrin inhibits bone metastasis of small cell lung cancer - Na Li; Jian-ping Zhang; Shan Guo; Jie Min; Li–li Liu; Hai-chuan Su; Ying-ming Feng; He-long Zhang (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Association of type 2 diabetes susceptibility genes (TCF7L2, SLC30A8, PCSK1 and PCSK2) and proinsulin conversion in a Chinese population - Xiaoya Zheng; Wei Ren; Suhua Zhang; Jingjing Liu; Sufang Li; Jinchao Li; Ping Yang; Jun He; Shaochu Su; Ping Li (Molecular Biology Reports, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

Antithrombotic lipids from Semen Persicae - Nian-Yun Yang; Li Liu; Wei-Wei Tao; Jin-Ao Duan; Xun-Hong Liu; Su-Ping Huang (Natural Product Research, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Development, characterization, and cross-species/genera transferability of SSR markers for rubber tree (Hevea brasiliensis) - Fei Yu; Bao-Hua Wang; Su-Ping Feng; Jing-Yi Wang; Wei-Guo Li; Yao-Ting Wu (Plant Cell Reports, 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

Identification of molecular markers linked to the genes for purple grain color in wheat (Triticum aestivum) - Xing-Pu Li; Su-Que Lan; Ye-Lun Zhang; Yu-Ping Liu (Genetic Resources and Crop Evolution, 2010)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

A tomato bZIP transcription factor, SlAREB, is involved in water deficit and salt stress response - Tsai-Hung Hsieh; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Sanjaya; Yi-Chien Tsai; Ming-Tsair Chan (Planta, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

The interaction between interferon-induced protein with tetratricopeptide repeats-1 and eukaryotic elongation factor-1A - Hong-Tao Li; Yong-Ping Su; Tian-Min Cheng; Jian-Ming Xu; Jie Liao; Ji-Chuan Chen; Chang-You Ji; Guo-Ping Ai; Jun-Ping Wang (Molecular and Cellular Biochemistry, 2010)

A Mediated Glucose Biosensor Incorporated with Reverse Iontophoresis Function for Noninvasive Glucose Monitoring - Congo Tak-Shing Ching; Tai-Ping Sun; Su-Hua Huang; Hsiu-Li Shieh; Chung-Yuan Chen (Annals of Biomedical Engineering, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Vegetation recovery monitoring over the waste dump in Haizhou opencast coalmine area, China, during 1975–2000 using NDVI and VF index - Wei Su; Zhong-Ping Sun; Dao-Liang Li; Raaj Ramsankaran; Xiang Zhu; Xiang-Yun Guo (Journal of the Indian Society of Remote Sensing, 2009)

Prevalence of human metapneumovirus in hospitalized children with respiratory tract infections in Tianjin, China - Xiao-yan Li; Jin-ying Chen; Mei Kong; Xu Su; Yan-ping Yi; Ming Zou; Hua Zhang (Archives of Virology, 2009)

Drepanocladus longifolius (Amblystegiaceae), an addition to the moss flora of King George Island, South Shetland Islands, with a review of Antarctic benthic mosses - Su-Ping Li; Ryszard Ochyra; Peng-Cheng Wu; Rodney D. Seppelt; Ming-Hong Cai; Hai-Ying Wang; Cheng-Sen Li (Polar Biology, 2009)

Notch signaling regulates the FOXP3 promoter through RBP-J- and Hes1-dependent mechanisms - Hai-Feng Ou-Yang; Hong-Wei Zhang; Chang-Gui Wu; Ping Zhang; Jian Zhang; Jun-Chang Li; Li-Hong Hou; Fei He; Xin-Yu Ti; Li-Qiang Song; Su-Zhen Zhang; Lei Feng; et al. (Molecular and Cellular Biochemistry, 2009)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Identification and expression analysis of hepcidin-like cDNAs from pigeon (Columba livia) - Yu Ming Fu; Su Ping Li; Yue Feng Wu; Yan Zhong Chang (Molecular and Cellular Biochemistry, 2007)

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

Development of EST-SSR in foxtail millet (Setaria italica) - Xiao-Ping Jia; Yun-Su Shi; Yan-Cun Song; Guo-Ying Wang; Tian-Yu Wang; Yu Li (Genetic Resources and Crop Evolution, 2007)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Effects of different Rht-B1b, Rht-D1b and Rht-B1c dwarfing genes on agronomic characteristics in wheat - Xing-Pu Li; Su-Que Lan; Yu-Ping Liu; M. Gale; T. Worland (Cereal Research Communications, 2006)

A study on cellular automata based on relational databases and spatio-temporal simulations of culture diffusion - Ping Luo; Qing-yun Du; Su-fang He; Sen Li; Gallagher Michael; Hui-en Niu (Chinese Geographical Science, 2002)